A new polarization image demosaicking algorithm by exploiting inter-channel correlations with guided filtering - Liu, Shumin (2021)
This paper presents a fast and effective polarization image demosaicking algorithm, which explores inter-channel dependency of Stokes parameters for the minimization of residual aliasing artifacts after cubic spline interpolation. A guided filtering approach is used for denoising. An optimization based on the confidence level of the aforementioned guided filtering, the correlations between the demosaicked image and input, as well as the total intensity, angle and degree of linear polarization, is constructed and solved with Newton’s method. Experimental results demonstrate that the proposed algorithm can surpass the existing methods in terms of both objective root mean squared error and structural similarity index by at least 36.0% and 3.4%, respectively, and by close visual inspection of the clarity of objects in the angle and degree of linear polarization images. The proposed algorithm consists of only convolutions and elementwise operations, making it fast and parallelizable for efficient GPU acceleration. An image of size 512×612×4 can be processed within 10 s on i7-6700k CPU, and gains further 5 times speedup with M4000M GPU.